Prospecção de genótipos de fava com características produtivas e de resistência ao ácaro Tetranychus neocaledonicus - Nere, Daniel Rodrigues (2020)
The lima bean (Phaseolus lunatus) is one of the main food sources to fight hunger in the tropical and subtropical regions of the world. In Brazil, despite the great genetic variability found, this potential is still few explored, national productivity does not exceed 520 kg /hectare, which demonstrates the need for research aimed at selecting genotypes with productive characteristics and resistance to pests that may contribute to the formation of cultivars In this context, this research aimed to: a) provide information on the biometric aspects of seeds and plants of lima bean varieties; b) to characterize plants and seeds of local varieties of lima bean and to estimate their genetic divergence; and c) identify and evaluate the resistance of varieties to the mite Tetranychus neocaledonicus. The results showed great genetic variability of the lima bean varieties, based on productive characteristics (mostly of productive importance) 9 possible classifications were obtained, while based on the color of the seed coat 10 possible classifications were obtained. In the genetic divergence, the most promising crosses were the genotypes IFCE-083 and IFCE-090 with the genotypes IFCE-012, IFCE-038, IFCE-043, IFCE-050, IFCE-055, IFCE-082, IFCE-084, IFCE-085, IFCE -091 and IFCE-093, which have complementary productivity relationships. Regarding resistance, the IFCE-090 genotype negatively affected the biological and population parameters of the mite, presenting as a defense mechanism the resistance by antibiosis, showing the potential to be added to crossbreeding groups in order to obtain resistant cultivars to be used in integrated pest management. In summary, lima bean varieties were characterized in terms of biometric, productive and resistance to T. neocaledonicus mite. Such information can be used to obtain more productive varieties and/or with resistance to the pest mite.